Effect of a Specialized Classroom Counseling Intervention on Increasing Self-Efficacy among First-Grade Rural Students. (2017) - Bardhoshi, Gerta; Duncan, Kelly; Erford, Bradley T.
This preliminary research examined the effectiveness of a classroom counseling intervention on student self-efficacy development. Five first-grade classrooms in a rural school with high rates of economic disparity were randomly assigned to either a set of 12 specialized lesson emphasizing self-efficacy or lessons from the existing core curriculum. Teachers completed the Self-Efficacy Teacher Rating Scale (SETRS) for each student as a pretest and 3 months following the classroom intervention. A significant mean score difference posttreatment [F(1, 77) = 19.57, p < .05, η 2 = .209; d = .58(CI95 = .36 - .80)] supports the effectiveness of this intervention in improving the self-efficacy of first-grade students.